Monitoring costs of MNC: an agency theory perspective. - Mustapha, Mazlina (2011)
This paper investigates the agency costs of multinational companies (MNC) in relation to agency theory in Malaysian business environment. Using the data of 235 MNCs, this study explores their demand for monitoring costs and these companies' preferences between the monitoring costs components. The data is collected using primary and secondary data. Multiple regression analysis and independent t-tests are conducted to analyze the data. The result indicates that multinational companies demand significantly higher monitoring costs compared to domestic companies. However, the relationship between these companies and their preference between the components of the monitoring mechanisms, that is between directorship and auditing as their monitoring mechanism is not significant. But when the auditing components are further investigated, it reveals that multinational companies would demand more external audit costs compared to internal audit costs. These results are supported by series of independent t-test which indicate that there are significant differences between the demands for monitoring of multinational companies as compared to their domestic counterparts.